Membangun Aplikasi Natural Language Processing Menggunakan Instant Messenger Untuk Informasi Bencana (Publikasi Eksternal, 2013)
Instant messaging is a communication facility to the users of internet chat. By using this facility, the user can communicate by sending a text message to another user. In addition, Instant Messaging also serves to exchange files in a peer to peer. Availability of vast resources and varied, as well as the rapid development of techniques Natural Language Processing (NLP), Information Extraction (IE) and Information Retrieval (IR) greatly influenced the development of QA (Question Answering) system, which used to only be able to answering the questions are limited to a field (domain) specific to based on structured information sources such as databases, up to now can answer different types of questions, referring to a collection of information from unstructured text.This research is utilizing receipts Instant Messenger Google Talk service to provide information to your questions on the online disaster. The system works by utilizing a database of various sites on the Internet. The research is fitted with a QA application system using disaster information crawler results of some catastrophic news site